2014
DOI: 10.1111/jora.12145
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relations of Parental Influences and Adolescent Career Aspirations and Actions in a Collectivist Society

Abstract: Using social cognitive career theory as a framework, we examined the longitudinal effects of proximal parental contextual influences on career aspirations and actions in a collectivist context. We used a sample of 954 Indonesian high school students and measured parental career expectations, adolescent-parent career congruence, self-efficacy, outcome expectations, career aspirations, planning and exploration, twice, 6 months apart. The best-fitting model was reciprocal, with the results showing that parental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 67 publications
(118 reference statements)
7
62
1
6
Order By: Relevance
“…This finding extends previous research which found a positive relationship between academic fit and academic satisfaction [3]. We also found a positive relationship between adolescent-parent career congruence and career exploration, suggesting that students who are congruent with parents regarding career matters are more likely to engage in career exploration, which is consistent with previous findings [17,18]. Academic fit was correlated positively with career exploration, directly, and indirectly via congruence.…”
Section: Adolescent-parent Career Congruence As Mediatorsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding extends previous research which found a positive relationship between academic fit and academic satisfaction [3]. We also found a positive relationship between adolescent-parent career congruence and career exploration, suggesting that students who are congruent with parents regarding career matters are more likely to engage in career exploration, which is consistent with previous findings [17,18]. Academic fit was correlated positively with career exploration, directly, and indirectly via congruence.…”
Section: Adolescent-parent Career Congruence As Mediatorsupporting
confidence: 90%
“…This indicates that congruence serves as a partial mediator between academic fit and career exploration, suggesting that academic fit affects career exploration by directly motivating individuals to involve in career exploration activities, and also by facilitating congruence. Findings of this study are in line with the personenvironment fit theories [1,2]and also expand previous studies regarding the correlates of adolescent career exploration in collectivist contexts [17,18].…”
Section: Adolescent-parent Career Congruence As Mediatorsupporting
confidence: 87%
“…Parents tend to socialize their children in an attempt to realize their own expectations, and thus, socialization goals are shaped by parents’ personal beliefs and attitudes (Darling & Steinberg, ; Grusec & Goodnow, ). Consistent with this proposition, a notable body of research has indicated that parental career expectations, defined as parental attitudes and hopes for children's future occupational achievements, are associated with adolescents’ career developmental outcomes, including career explorations, concerns, and indecisions (Leung, Hou, Gati, & Li, ; Meece, Askew, Agger, Hutchins, & Byun, ; Sawitri, Creed, & Zimmer‐Gembeck, ; Sawitri et al., ). In general, parents with higher (yet not extremely high) levels of career expectations tend to be more motivated and involved in providing children with career‐related resources, guidance, and support to promote children's career aspirations, planning, explorations, and actions (Meece et al., ; Sawitri et al., ; Sawitri et al., ).…”
Section: Career‐related Parental Processes and Adolescents’ Career Dementioning
confidence: 95%
“…The existing work, however, is limited in its reliance on primarily variable‐centered approaches applied to predominantly Western samples (Sawitri et al., ). In “real” daily lives, parents often simultaneously engage in a mixture of career‐related parental processes that are typically interconnected in various meaningful ways (Dietrich & Kracke, ).…”
Section: Career‐related Parental Processes and Adolescents’ Career Dementioning
confidence: 99%
“…Penelitian sebelumnya menunjukkan bahwa aspirasi karir mengarahkan individu untuk melakukan perencanaan karir, dan dalam jangka panjang berkorelasi positif dengan eksplorasi karir (Sawitri, Creed, & ZimmerGembeck, 2014;Sawitri, Creed, & ZimmerGembeck, 2015). Aspirasi karir merupakan tujuan atau cita-cita individu dalam bidang karir (Rojewski, 2005).…”
Section: Pendahuluanunclassified